Humoral antibody response following mRNA vaccines against SARS-CoV-2 in solid organ transplant recipients; a status after a fifth and bivalent vaccine dose - Christophorou, Emma; Nilsson, Anna Christine; Petersen, Inge; Lindvig, Susan O.; Davidsen, Jesper R.; Abazi, Rozeta; Poulsen, Mikael K.; Pedersen, Rune M.; Justesen, Ulrik S.; Johansen, Nicolai E.; Bistrup, Claus; Madsen, Lone W.; et al. (Frontiers in Immunology, 2023)
In solid organ transplant (SOT) recipients, the humoral response following COVID-19 vaccination is reduced, as a result of their immunosuppressed treatment. In this study, we investigated antibody concentrations after booster vaccinations until the fifth dose, the latter by monovalent or bivalent BA1 or BA4/5 vaccines. In addition, we evaluated the efficacy of vaccination by recording breakthrough infections, hospitalizations and deaths.This prospective cohort study included 438 SOT recipients (>18 years) vaccinated with mRNA vaccines against COVID-19 from January 2021 until March 2023. Blood samples were drawn before and after each vaccination and tested for SARS-CoV-2 spike RBD IgG antibodies with the lowest and highest cut-off on 7.1 and 5,680 BAU/mL, respectively. Vaccine information, breakthrough infections, and hospitalizations were collected from the medical records.Most participants received BNT162b2 and 61.4 % received five vaccine doses. The response proportion in SOT recipients increased from 86.7 % after the fourth dose to 93.0 % following the fifth dose. Antibody concentration decreased with 142.7 BAU/mL between the third and fourth dose (median 132 days, Quartile 1: 123, Quartile 3: 148) and 234.3 BAU/mL between the fourth and fifth (median 250 days, Quartile 1: 241, Quartile 3: 262) dose among those without breakthrough infection (p=0.34). When comparing the Omicron BA.1 or Omicron BA.4/BA.5 adapted vaccines, no significant differences in antibody concentration were found, but 20.0 % of SOT recipients receiving a monovalent fifth vaccine dose had a breakthrough infection compared to 4.0 % and 7.9 % among those who received BA.1 and BA.4/BA.5 adapted vaccines, respectively (p=0.04). Since January 2021, 240 (54.8 %) participants had a breakthrough infection, and 22 were hospitalized, but no deaths were observed.The fifth COVID-19 vaccine dose raised antibody response to 93.0 % of the study population.Additional booster doses, as well as bivalent vaccines, led to higher levels of antibody concentration 3 in SOT recipients. We found a lower incidence of breakthrough infections among SOT recipients after receiving a bivalent vaccine as a fifth dose compared to those receiving a monovalent dose. Antibody concentrations did not wane when the time between doses were prolonged from four to eight months.